Implementasi PSAK NO. 106 Akuntansi Musyarakah Pada Produk Pembiayaan Kepemilikan Rumah - Soleha, Soleha (Disclosure: Journal of Accounting and Finance, 2021)
As on of the Business measuring tools, accounting is inseparable from Business Activities owing to its function to provide information about the financial condition and as a medium of accountability between parties. Therefore, accounting standards are essentially required to prevent from any kinds of abuse of Authority and Disputes. Some Research findings highlights that most of the banks have not implemented accounting standards. This Research uses qualitative normative approach by researching financing managers as the Research subjects representing the bank institution. The data Wet collected through instrument of interview and documentation. The data Wet analyzed with qualitative analysis. In practice, this bank has complied with accounting standards. Such statement of accounting standards applied to home financing Products is its conformity with statement of Financial Accounting Standards (PSAK) No. 106 on Musyarakah Accounting.